2012
DOI: 10.1371/journal.ppat.1002526
|View full text |Cite
|
Sign up to set email alerts
|

Different Chitin Synthase Genes Are Required for Various Developmental and Plant Infection Processes in the Rice Blast Fungus Magnaporthe oryzae

Abstract: Chitin is a major component of fungal cell wall and is synthesized by chitin synthases (Chs). Plant pathogenic fungi normally have multiple chitin synthase genes. To determine their roles in development and pathogenesis, we functionally characterized all seven CHS genes in Magnaporthe oryzae. Three of them, CHS1, CHS6, and CHS7, were found to be important for plant infection. While the chs6 mutant was non-pathogenic, the chs1 and chs7 mutants were significantly reduced in virulence. CHS1 plays a specific role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
192
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(206 citation statements)
references
References 85 publications
10
192
0
2
Order By: Relevance
“…In the present study, in both of the A. infectoria strains tested, CHSE, a class VII Chs that contain an MMD, was overexpressed in response to caspofungin and nikkomycin Z. Class VII enzymes have also been demonstrated to be essential for virulence in several plant pathogens (21,61) and, together with class V Chs, seem to play a crucial structural role in the human pathogen A. fumigatus and in A. nidulans (62,63).…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…In the present study, in both of the A. infectoria strains tested, CHSE, a class VII Chs that contain an MMD, was overexpressed in response to caspofungin and nikkomycin Z. Class VII enzymes have also been demonstrated to be essential for virulence in several plant pathogens (21,61) and, together with class V Chs, seem to play a crucial structural role in the human pathogen A. fumigatus and in A. nidulans (62,63).…”
Section: Discussionmentioning
confidence: 47%
“…This multiplicity of isoforms implies specificity of function, as it occurs in other fungi (21,55). We found that the expression of some CHS genes was altered, depending on the antifungal and on the A. infectoria strain.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…[8][9][10][11][12][13][14] These investigations indicate that chitin synthases with MMD play important roles in hyphal tip growth and the invasion of host cells. Since the yeasts Saccharomyces cerevisiae and Schizosaccharomyces pombe and the dimorphic yeast Candida albicans do not possess these orthologs in their genomes, chitin synthases with MMD are likely to play critical roles in polarized growth, especially in filamentous fungi.…”
mentioning
confidence: 92%